Malay epic and historiography literature students' perception towards interactive online interaction - Noor Muhammad, Salmah Jan; Che Puteh, Che Nuraini; Abd Rahim, Normaliza (Canadian Center of Science and Education, 2019)
Technology is a need among modern community that ensures new knowledge and can be shared and utilized together. In teaching and learning, technology usage can be considered as a tool that can improve students’ cognitive, psychomotor and effective, also can interconnect with each other. Without technology, the learning world can be classified as a backward era. Therefore, through the interactive connection, learning can be more interesting and effective. Thus, the effectiveness of students’ needs will be measured either interactive connection that attracts students’ interest or vice-versa. Therefore, the objectives of the study are to determine the response towards online teaching interactive, also to analize and summarize UPM students online interactive connection by using the Technology Acceptance Model (TAM). This research applied online questionnaire by using the Monkey Survey website. About 94 Univeriti Putra Malaysia students from BBK 3311 Malay Epic and Historiography Literature course were choosen as research samples. The results of the study showed that majority of the samples are satisfied with the technology interactive method that had been introduced in this subject through Putramooc Malay Art platform. It is hoped that this research can help to identify the technology interactive connection through the most dominant multimedia and can be applied by the parties involved.